Women’s Participation in Rural Development (A Gender Study on the Women’s Involvement in Musrenbangdes in the Villages District Blayu and Patokpicis Wajak Malang) - Ahmad Jaenudin; Darsono Wisadirana; Sholih Mu’adi (Wacana Journal of Social and Humanity Studies, 2017)
The patriarchate pattern in the rural society limits the right and obligaten among women to contribute in rural development through musrenbangdes. The main problem of the research is how is women participation in rural development through  musrenbangdes?  The aim of this research is to analyze the positions, ferms, and factors that influence the women participation. This is a qualitative research, using PRA Robert Chambers approachment, snowballing sampling technigue,  primary data collecting technigue through;  observation, interview, FGD. And secundary data collecting through;  documents, data validity  examination technique, source based triangulation, and data management technique; Miles and Huberman interactive analysis. Results; 1) Contribution position in administrative and consumption field, 2) Direct contribution in programme planning and programme accomplishment, indirect contribution as a participator and moral supporting, 3) Supporting factors; women awareness, socialization and invitation, chance to be part of stakeholder, male support. As the carrier factors;  unsuitable schedule of the musrenbangdes for the women, the women multiple roles, lack of socialization and invitation, low level of education. Summary, the inferior position and women minimun contribution due to some internal and external factors from the women side themselves. As consideration, it is necessary for the rural government to increase the socialization, the awareness of the female , increasing male support,  and the importance of women rural leader.